Kinematic and thermodynamic operational analysis of rhombic-drive Stirling engine prototype - Mohd Farid, Zainudin; Rosli, Abu Bakar; Kadirgama, Kumaran; Gan, Leong Ming (Institute of Physics Publishing, 2020)
This operational analysis is aimed for the next development of rhombic-drive beta-configuration Stirling engine prototype. The kinematic analysis focused on the adjustment of crank radius and connecting rod length, for achieving optimum phase angle setting and suitable eccentricity ratio based on geometrical constraints. The isothermal thermodynamic analysis is carried out to predict the engine performance between the baseline and proposed design parameters. The reciprocating displacement of moving pistons, volumetric displacement, cyclic pressure, energy produced and thermal efficiency are derived and solved. The results show that the reduction of crank radius increases the eccentricity ratio, while both reduction of connecting rod length and crank radius increase the phase angle setting. It is found that as the phase angle setting increase, the engine power output and thermal efficiency increase. The magnitudes of engine power and thermal efficiency may be elevated by modifying the geometrical design and operating condition.